TINJAUAN LITERATUR: PENDIDIKAN USIA DINI UNTUK MENGURANGI TERJADINYA KEKERASAN SEKSUAL PADA ANAK - Nining Loura Sari (STIKes Maharani Malang, 2023)
Introduction: Education is the foundation of a nation's future sustainability and its ability to become a more advanced and developing nation. One of the most important educations to be given to children from an early age is sex education. Implementation of sex education in early childhood education is very important to prevent sexual violence in children. The method used in this study was the journal literature review method in the data base using keywords according to topic and obtaining six journals, but only four journals that matched the inclusion criteria. Results and analysis: The results of the study show that early childhood education to prevent sexual violence includes knowledge, understanding, and recognition related to various kinds of early childhood education materials. Discussion: Early childhood education programs to reduce the occurrence of sexual violence in children should be delivered in schools so that the information is useful for children according to their developmental phase and can protect their bodies from threats of sexual violence. Keywords: Early childhood education, Sexual Violence on Children